THE INFLUENCE OF WORK FROM HOME AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE AT PT. BNI (PERSERO) TBK SUDIRMAN PEKANBARU BRANCH - Norawati, Suarni; Putera, Eka (ITB AAS Indonesia Surakarta, 2024)
Banks are institutions that play a mediating role in collecting and distributing funds. To carry out this main function, banking management really needs maximum employee performance. Employee performance achievements are influenced by other factors, which in this research only look at the influence of implementing the Work From Home (WFH) policy and work discipline on job satisfaction, the direct influence of employee performance, the influence of job satisfaction on employee performance, the direct influence of WFH and work discipline on performance and the influence of WFH and work discipline on performance through employee job satisfaction at PT Bank BNI (Persero), Tbk Pekanbaru Branch. To achieve the research objectives, primary and secondary data are required which are obtained using questionnaires, interviews, observations and research files. The sample for this research was 80 employees and the data analysis tool was carried out using SEM (Structural Equation Model) which was processed using the SmartPLS version 3.00 program package. The results of this research conclude that the application of WFH and work discipline has a significant effect on employee job satisfaction, the application of WFH policies does not have a significant effect on employee performance, job satisfaction has a significant effect on employee performance, there is an influence of the implementation of WFH policies and work discipline on performance through job satisfaction of PT employees Bank BNI (Persero), Tbk Pekanbaru Branch. Keywords: Performance, Job Satisfaction, WFH, Work Discipline